A Pioneering New Form of Balochi poetry in Karim Dashti’s Ghazal - Khan, Dolat; Mehr, Rahim Bakhsh (Pakistan Languages and Humanities Review, 2025)
The objective of the paper is to explore a distinct poetic tradition within Balochi literature—one that pays homage to culture and homeland through a unique synthesis of ancient Balochi balladry and the Sufi-infused sensibilities of the Persian ghazal. While the Persian ghazal often centers on divine or romantic love, this Balochi tradition redirects those emotional and spiritual energies toward the land itself. The study has used a method of textual analysis and close reading to obtain results. Rooted in the classical dastan—a narrative and epic poetic form—this tradition simultaneously absorbs the lyrical intensity and mystic devotion characteristic of Persian literary aesthetics. This paper focuses specifically on the poetry of Karim Dashti, analyzing how his verses exemplify and advance this powerful form of cultural and emotional expression. The study can be further expanded to include a close reading of Zahoor Shah Hashmi and Atta Shad`s poetry.